Endothelialization of drug eluting stents and its impact on dual anti-platelet therapy duration. (March 2015) - Habib, Anwer; Finn, Aloke V.
Graphical abstract: Abstract: Coronary artery disease is a leading cause of death and disability worldwide with contemporary treatment strategies employing both optimal medical therapy and catheter based percutaneous coronary intervention (PCI) with drug eluting stents (DES). While DES have dramatically reduced restenosis rates, their use has been associated with an increased risk of late stent thrombosis and accelerated neointimal atherosclerosis (i.e. "neoatherosclerosis") both major contributors to late stent failure. The underlying substrate of late DES failure is likely related to vascular endothelial dysfunction such as poor endothelial regrowth and barrier function (i.e. "endothelial healing"). Initial concerns with 1st generation DES have lead to improvements in mechanical and biologic properties of current 2nd generation DES, which inhibit endothelial regrowth to a lesser extent, lessening late stent failure and resulting in an overall improved safety profile. Current guidelines recommend duration of at least one year of dual anti-platelet therapy with aspirin and a thienopyridine agent such as clopidogrel or prasugrel as sufficient to prevent late thrombotic complications. Recent studies, however, suggest a shorter duration of dual anti-platelet therapy may be equally as safe and efficacious in preventing stent thrombosis with newer generation DES. However, higher risk populations such as patients receiving 1st generation DES or those with increased risk for future ischemic events may benefit from a longer duration (i.e. 30 months) of DAPT to prevent major cardiovascular events with the caveat that such an approach may be associated with an increased risk for bleeding. This review examines the vascular responses to 1st and second generation DES and recent clinical trials examining DAPT duration.